More Common Than You Think: Common Variable Immune Deficiency - Aderinto, Abimbola; Mouli, Vibav; Resar, Danielle F.; Resar, Linda M. S. (Case Reports in Hematology, 2013)
We report a challenging case of a 16-year-old male who presented with thrombocytopenia and eluded a definitive diagnosis for over 2 years. He was initially diagnosed with a viral illness, although he later developed adenopathy and splenomegaly. An evaluation by an oncologist was unrevealing. He worked on a farm with livestock exposure and was later diagnosed with an atypical, zoonotic infection. Despite appropriate antibiotic therapy, the thrombocytopenia and splenomegaly persisted. Further evaluation revealed that he has a relatively common immunologic disorder. He is currently doing well on appropriate therapy for this disorder.